The Development of Interactive Learning Media of Parabolic Motion Lesson Materials with Patil Lele Traditional Games - Jamalludin - Jamalludin; Rif'ati Dina Handayani; Lailatul - Nuraini (Universitas Lambung Mangkurat, 2021)
Indonesian cultures are starting to fade due to technological developments. One of the solutions is by introducing Indonesian cultures to students at school. This research aimed to generate an effective and valid traditional culture-based interactive learning media, therefore it can be used in learning physics. The learning media that was developed by the researcher was an interactive learning media on the parabolic motion subject with 3-dimensional animation of Patil Lele's traditional game. This research was development research with the Thiagarajan model, which has been modified into 3D (Define, Design, and Develop). The data were collected by using an expert validation sheet and a student test. The results showed that the learning media was valid and effective, with an average percentage of the validator's assessment 90.8% and the percentage of student learning completeness 82.35%. Referring to the analysis results that has been carried out on the media that was developed, it was included as a valid and effective category for use, therefore the learning media product is able to be used in learning physics.